2020
DOI: 10.3390/cells9102277
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the CX3CL1/CX3CR1 Axis in Neurological Disorders

Abstract: Fractalkine (FKN, CX3CL1) is a transmembrane chemokine expressed by neurons in the central nervous system (CNS). CX3CL1 signals through its unique receptor, CX3CR1, that is expressed in microglia. Within the CNS, fractalkine acts as a regulator of microglia activation in response to brain injury or inflammation. During the last decade, there has been a growing interest in the roles that the CX3CL1/CX3CR1 signaling pathway plays in the neuropathology of a diverse array of brain disorders. However, the reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
116
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(131 citation statements)
references
References 128 publications
3
116
0
Order By: Relevance
“…Several studies have shown its role in the epilepsy pathogenesis and concomitant cell death. Blocking of CX3CL1/CX3CR1 signaling pathway by antibodies reduces microglial activation and neurodegeneration caused by an electrical epileptic seizure in rodents [43].…”
Section: Chemokines Fractalkin (Fkn Cx3cl1)mentioning
confidence: 99%
“…Several studies have shown its role in the epilepsy pathogenesis and concomitant cell death. Blocking of CX3CL1/CX3CR1 signaling pathway by antibodies reduces microglial activation and neurodegeneration caused by an electrical epileptic seizure in rodents [43].…”
Section: Chemokines Fractalkin (Fkn Cx3cl1)mentioning
confidence: 99%
“…CX3CL1 (Fractalkine) is a ligand for chemokine receptor CX3CR1. Multiple lines of evidence suggest that CX3CL1/CX3CR1 axis plays important roles in the neuropathology of various brain disorders such as cerebral ischemia, epilepsy, and AD (Reviewed in Pawelec et al, 2020). Bolos et al (2017) reported that CX3CR1 deficiency decreases the internalization of 2N4R tau monomer in microglia both in vitro and in vivo.…”
Section: The Interaction Of Tau With Membrane Proteinsmentioning
confidence: 99%
“…Specific presynaptic (SNAP25) and postsynaptic (PSD95) proteins were identified inside microglial processes following synaptic contacts, by confocal or immune-gold electron microscopy, respectively ( 18 ). Furthermore, disrupting the fractalkine (Cx3cl1/Cx3cr1)-mediated communication between microglia and neurons in an otherwise healthy mouse, resulted in brain circuits persisting as immature into adulthood ( 18 , 180 , 181 ). In 2012, the Stevens' lab at Boston Children's Hospital, found that, in the newborn mouse visual system, microglia can engulf synapses in the lateral geniculate nucleus (LGN) through a process mediated by both complement and neuronal activity.…”
Section: Experimental Settings For Investigating Synapse Elimination mentioning
confidence: 99%